2017
DOI: 10.1080/14767058.2017.1359831
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sleep quality among pregnant women in China: a cross-sectional survey

Abstract: Sleep disorder is very common in pregnant women from China. Depressive symptoms, increased maternal age, and gestational age are determinants of sleep quality. These determinants can assist healthcare professionals in preventative intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
9
30
3
1
Order By: Relevance
“…Maternal age was identified as a predictor of poor sleep quality in our study, suggesting that sleep quality of pregnant mothers declines as their age increases. This was in agreement with the results of studies conducted in China [ 17 ] and Turkey [ 13 ]. As a potential risk factor, women with increased age were more likely influenced by physiological and psychological factors, hence leading to the decline of sleep quality [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Maternal age was identified as a predictor of poor sleep quality in our study, suggesting that sleep quality of pregnant mothers declines as their age increases. This was in agreement with the results of studies conducted in China [ 17 ] and Turkey [ 13 ]. As a potential risk factor, women with increased age were more likely influenced by physiological and psychological factors, hence leading to the decline of sleep quality [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…When compared with the first trimester of pregnancy, significant decline in sleep quality were observed in the second and third trimester of pregnancy. This is similar with the findings of studies conducted in Turkey [ 4 ], Pakistan [ 24 ] and China [ 17 ]. This might be due to the increment of hormonal changes, maternal stress and fetal movement as gestational age increases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with previous studies and a recent meta-analysis (Naud, Ouellet, Brown, Pasquier, & Moutquin, 2010;Sedov, Cameron, Madigan, & Tomfohr-Madsen, 2018;Sivertsen, Hysing, Dørheim, & Eberhard-Gran, 2015). Yang et al (2018) also found that 87% of pregnant women experienced sleep disorder (PSQI score >5). Poorer global sleep quality, subjective sleep quality, lower sleep efficiency, and sleep disturbances were most prevalent during third trimester.…”
Section: Discussionsupporting
confidence: 93%